Base rate comparison of suboptimal scores on the RBANS effort scale and effort index in Parkinson's disease. Issue 7 (2nd October 2016) - Carter, Kirstine R.; Scott, James G.; Adams, Russell L.; Linck, John
Abstract: Objective: The effort index (EI) and the effort scale are commonly used embedded effort indicators on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). This investigation examined the rates of suboptimal scores on the EI and effort scale in a Parkinson's disease (PD) sample.Method: One hundred and sixty-three participants who have been diagnosed with PD by a board-certified neurologist were included in the study. The base rate of suboptimal scores on the EI and effort scale was calculated for the entire group.Results: On average, participants were 66.8 years of age ( SD  = 9.5) and had a mean education of 13.5 years ( SD  = 2.79). The mean Mini-Mental State Examination score was 27.0 ( SD  = 3.1). Overall, 8% of participants scored below the cut-off for optimal performance on the EI while 62.6% performed in the suboptimal range for the effort scale.Conclusion: The utility of the EI and the effort scale in PD populations warrants further examination. Additionally, results demonstrate the need for validation of embedded RBANS effort measures in various disease populations.